2009
DOI: 10.1002/cssc.200900066
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Triggered Thermoelectric Conversion Based on a Carbon Nanotube–Polymer Hybrid Gel

Abstract: Lights? Nanotubes? Action! A hydrogel comprising lysozymes, poly(ethylene glycol), phospholipids, and functionalized single-walled carbon nanotubes is employed for light-driven thermoelectric conversion. A photoinduced thermoelectric conversion module based on the hydrogel functions as a novel electric power generator (see image). This concept may find application in various industries, such as robotics and aerospace engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…This was largely attributed to the low thermal stability of the PAA hydrogel. [14] Fukushima et al recently reported SWNT-roomtemperature ionic liquid (RTIL) gel composites for use in electronics and as actuators. [15,16] RTILs, especially those based on the n-alkylimidazolium cation, are emerging as alternatives to the conventional organic solvents used in chemical processes.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This was largely attributed to the low thermal stability of the PAA hydrogel. [14] Fukushima et al recently reported SWNT-roomtemperature ionic liquid (RTIL) gel composites for use in electronics and as actuators. [15,16] RTILs, especially those based on the n-alkylimidazolium cation, are emerging as alternatives to the conventional organic solvents used in chemical processes.…”
mentioning
confidence: 99%
“…[15,[17][18][19] The voltage and electrical power generated by the thermoelectric convertors increased 3-and 10-fold, respectively, compared to the previously reported nanotube-polymer hydrogel composite modules. [14] We assume that the photothermal stability of the RTIL yields greater voltage and electrical power than the previously reported PAA-based hydrogels because the destruction of the PAA gel matrix causes inefficient heating by the diffuse reflection of light. [14] These results clearly demonstrate that the SWNT-RTIL gel composites sufficiently generate electrical energy and that they are highly photothermostable.…”
mentioning
confidence: 99%
See 3 more Smart Citations